Multi-Component MHD Model of Hot Jupiter Envelopes - Andrey Zhilkin; Dmitri Bisikalo (Universe, 2021)
A numerical model description of a hot Jupiter extended envelope based on the approximation of multi-component magnetic hydrodynamics is presented. The main attention is focused on the problem of implementing the completed MHD stellar wind model. As a result, the numerical model becomes applicable for calculating the structure of the extended envelope of hot Jupiters not only in the super-Alfvén and sub-Alfvén regimes of the stellar wind flow around and in the trans-Alfvén regime. The multi-component MHD approximation allows the consideration of changes in the chemical composition of hydrogen–helium envelopes of hot Jupiters. The results of calculations show that, in the case of a super-Alfvén flow regime, all the previously discovered types of extended gas-dynamic envelopes are realized in the new numerical model. With an increase in magnitude of the wind magnetic field, the extended envelope tends to become more closed. Under the influence of a strong magnetic field of the stellar wind, the envelope matter does not move along the ballistic trajectory but along the magnetic field lines of the wind toward the host star. This corresponds to an additional (sub-Alfvénic) envelope type of hot Jupiters, which has specific observational features. In the transient (trans-Alfvén) mode, a bow shock wave has a fragmentary nature. In the fully sub-Alfvén regime, the bow shock wave is not formed, and the flow structure is shock-less.